2013
DOI: 10.1177/0044118x13483778
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sexual Orientation in School-Based Victimization

Abstract: School-based victimization is associated with poorer developmental, academic, and health outcomes. This meta-analytic review compared the mean levels of school-based victimization experienced by sexual minority youth to those of heterosexual youth, and examined moderators of this difference. Results from 18 independent studies (N = 56,752 participants) suggest that sexual minority youth experience moderately higher levels of school-based victimization compared to heterosexual youth (d = .33). This effect varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
139
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(157 citation statements)
references
References 67 publications
11
139
2
5
Order By: Relevance
“…Labelling an individual (correctly or incorrectly) as homosexual can have important social consequences as homosexual men and women may be subject to prejudice, discrimination, and abuse (Herek, 2009;Toomey & Russell, 2013). Furthermore, heterosexuals may attempt to create psychological distance between themselves and homosexuals (Tally & Bettencourt, 2008), and avoid being perceived as homosexual (Falomir-Pichastor & Mugny, 2009;Herek, 2002) or the object of homosexual desire (Buijs, Hekma, & Duyvendak, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Labelling an individual (correctly or incorrectly) as homosexual can have important social consequences as homosexual men and women may be subject to prejudice, discrimination, and abuse (Herek, 2009;Toomey & Russell, 2013). Furthermore, heterosexuals may attempt to create psychological distance between themselves and homosexuals (Tally & Bettencourt, 2008), and avoid being perceived as homosexual (Falomir-Pichastor & Mugny, 2009;Herek, 2002) or the object of homosexual desire (Buijs, Hekma, & Duyvendak, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have documented the unique minority-related stressors (e.g., bias-based victimization) that sexual minority adolescents encounter at school (Toomey & Russell, 2016), as well as the robust associations among these risk factors and poor health and academic outcomes (Collier, van Beusekom, Bos, & Sandfort, 2013; Russell, Sinclair, Poteat, & Koenig, 2012; Toomey, Ryan, Diaz, Card, & Russell, 2010). Similarly, others have documented the unique stressors that youth of color experience at school (e.g., racial/ethnic-based victimization, Lai & Tov, 2004; Robers, Kemp, Rathbun, Morgan, & Snyder, 2014; Russell et al, 2012), and that these risk factors are also associated with poor health and academic outcomes (Pachter & Coll, 2009; Umaña-Taylor & Updegraff, 2007).…”
mentioning
confidence: 99%
“…It is well documented that sexual minority students report greater victimization or bullying in school than heterosexual students (Poteat, Mereish, DiGiovanni, & Koenig, 2011; Shields, Whitaker, Glassman, Franks, & Howard, 2012; Toomey & Russell, 2013) and recent research has demonstrated that the increased victimization is partly responsible for mental health disparities in SMY (Burton et al, 2013). It is reasonable to extend the minority stress hypothesis to include school absenteeism because if school is perceived as a hostile environment for some SMY then they will be more likely to skip school.…”
mentioning
confidence: 99%
“…The higher prevalence of depression and anxiety symptoms in SMY (Marshal et al, 2011) and greater levels of victimization in school (Toomey & Russell, 2013) suggest that SMY may be at higher risk for school absenteeism because both mental health and victimization are associated with absenteeism (Poteat et al, 2011; Wood et al, 2012). There is relatively little research on school absenteeism among SMY and even less research that compares absenteeism among SMY and heterosexual youth.…”
mentioning
confidence: 99%